An overview on Vadimezan (DMXAA): The vascular disrupting agent. (24th January 2018) - Daei Farshchi Adli, Amir; Jahanban‐Esfahlan, Rana; Seidi, Khaled; Samandari‐Rad, Sonia; Zarghami, Nosratollah
Abstract : Vascular disrupting agents (VDAs), a group of cancer remedies, can cause a specific and irreversible destruction of established tumor vessels, and the complete halt of blood flow in the tumor. DMXAA (ASA404) or Vadimezan, a flavone‐acetic acid‐based drug, is the most promising VDAs that induces a rapid shutdown of blood flow in tumors but not in normal tissue. The exact mechanism of vascular disruption is unknown; however, proposed direct and indirect mechanisms of action for DMXAA comprises (i) inducing apoptosis in endothelial cells; (ii) hemorrhagic necrosis and ischemia in tumor; (iii) release of serotonin (5‐HT); (vi) stimulation of innate immune system; (v) production of inflammatory cytokines, for example TNF, IL‐6, GCSF, KC, IP‐10, and MCP‐1; (vi) activation of NFκB and p38 (MAPK); (vii) production of nitric oxide; and (viii) reducing tumor energetics and membrane turnover. Despite the remarkable results from preclinical and phase I/II, DMXAA has failed in phase III clinical trials. The reason for this surprising discrepancy, among others, was discovered to be STING receptor variations between mice and humans. In this review, the development, the mechanisms of DMXAA action, the clinical trials, the combination therapy, and the future of this drug will be discussed. Abstract : This review highlights the characteristics of clinically used vascular disrupting agent drug, vadimezan, DMXAA (ASA404). Also development, and mechanisms of DMXAA action, and also the clinical trials, the combination therapy and the future of this drug is discussed.